Neurofilaments in CSF As Diagnostic Biomarkers in Motor Neuron Disease: A Meta-Analysis - Li, Dawei; Shen, Dongchao; Tai, Hongfei; Cui, Liying (Frontiers in Aging Neuroscience, 2016)
Abstract Objective: Neurofilaments in CSF are promising biomarkers which might help in the diagnosis of motor neuron disease (MND). We aim to assess the diagnostic value of neurofilaments in CSF for MND. Methods: Pubmed, Emabase and Web of Science were searched for relevant studies systematically. Articles in English that evaluated the utility of neurofilaments in CSF in the diagnosis of MND were included. Data were extracted by two independent investigators. Diagnostic indexes for neurofilament light chain (NFL) and phosphorylated neurofilament heavy chain (pNFH) were calculated separately. Stata 12.0 software with a bivariate mixed-effects model was used to summarize the diagnostic indexes from eligible studies. Results: Five studies on NFL and eight studies on pNFH met inclusion criteria. For NFL, the pooled sensitivity and specificity were 81% (95% confidence interval [CI], 72%-88%) and 85% (95%CI, 76%-91%), respectively; the positive likelihood ratio (PLR) and negative likelihood ratio (NLR) were 5.5 (95%CI, 3.1-9.8) and 0.22 (95%CI, 0.14-0.35), respectively; the summary diagnostic odds ratio (DOR) was 25 (95%CI, 9-70), and the area under summary receiver operator characteristic curve (AUC) was 0.90 (95%CI, 0.87-0.92). For pNFH, the pooled sensitivity, specificity, PLR and NLR were 85% (95% CI, 80%-88%), 85% (95%CI, 77%-90%), 5.5 (95%CI, 3.6-8.4) and 0.18 (95%CI, 0.13-0.25) respectively; the DOR was 30 (95%CI, 16-58), and the AUC was 0.91 (95%CI, 0.88-0.93). Conclusion: Neurofilaments in CSF have a high value in the diagnosis of MND, though the optimal cutoff value remains to be further investigated.